The Beliefs of Parents’ and Teachers’ in Regard to Enabling Relationships between Disabled and Typically Developing (Asian Education Studies, 2017)
The purpose of this research was to explore and analyse ways in which parents and teachers view and help to develop friendships between disabled and typically developing preschool-aged children. Interviews were carried out with 18 parents and 10 teachers focusing on three main topics: description of relationships between special needs and typically developing children, and the significance of such; those methods used to foster these relationships, and any external impacting factors; and the nature of interactions between parents and teachers regarding these relationships. The children referenced in these interviews were of preschool age. Overall, it was found that parents in addition to teachers emphasised friendships between special needs and typically developing children, believing such relationships are emotionally beneficial to the children. Relationships were described as positive overall, with children enjoying each other’s company, engaging in common interests, meeting each other’s needs and expressing desires for each other’s company. Friendships were facilitated in various ways, including establishing ‘play dates’ or sending children to the same centre. Conflict-resolution was also encouraged in such relationships. Awareness-raising methods for these friendships can be drawn from the research, as well as methods for facilitating these relationships.